Minimum wages and competition: The case of the German roofing sector - Kornelius Kraft; Christian Rammer; Sandra Gottschalk (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
This paper analyses the effects of minimum wages on competition in the German roofing sector. The case is particularly interesting since this sector is faced with a uniform minimum wage despite significant regional disparities in productivity and wages. As a control industry we take the plumbing sector, which shows a similar market structure and demand trend but is not subject to a minimum wage. Employing a comprehensive firm panel data and using a difference-in-difference approach, we estimate the impacts of minimum wages on market entries and exits and firms' profitability. We find significant effects for East Germany which point to a substantial shift in industry structure. Minimum wages decreased both market entries and exits for roofing firms while they increased entries of sole traders. A decreasing number of non-sole traders lowered competition for this group of firms and helped them to increase profitability. The increasing share of sole traders may indicate some type of evasion strategy in eastern Germany, particularly since wages for skilled roofers declined towards the minimum wage. In the western part of the country minimum wages had no impact on competition.
urn:nbn:de:bsz:180-madoc-329011
Keywords: D04; J21; J38; L11; L22; L74; 330; Minimum Wage; Competition; Firm Performance; Labour Market Policy; Evasion Strategy; Sole Traders